The Influence of Work Motivation and Work Environment on Employee Performance at the Office of the Administrative Personnel Education and Training Center, Ministry of Religion of the Republic of Indonesia, Ciputat, South Tangerang - Supriyatmoko, Bayu; Dinantara, Mohamad Duddy (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
This research aims to analyze the influence of work motivation and work environment on employee performance at the Administrative Training Center Office of the Ministry of Religion, Ciputat, South Tangerang. Using a quantitative descriptive method, the study involves all 50 employees as the population and sample through saturated sampling. Data analysis includes multiple linear regression, correlation, and hypothesis testing. The results indicate that work motivation has a significant positive effect on employee performance, evidenced by a tcount of 5.012 > ttable 2.102 and a significance value of 0.000 < 0.05, with a contribution of 40.9%. Similarly, the work environment significantly influences performance, with a tcount of 6.016 > ttable 2.102 and a significance value of 0.000 < 0.05, contributing 44%. Simultaneously, work motivation and the work environment have a combined significant positive effect, shown by an fcount of 17.746 > ftable 3.195 and a significance of 0.000 < 0.05, with a combined contribution of 45.4%. The correlation coefficient of 0.656 indicates a strong relationship between work motivation, the work environment, and employee performance. Overall, the study confirms that these factors significantly enhance performance in the office